FENOMENA BILINGUALISME (INDONESIA-KOREA) DALAM DINAMIKA SOSIAL GEN Z DI SURABAYA - Diah Putri Anggraini (Jurnal PUBLIQUE, 2024)
In this research, several problems were studied, namely related to the process of generation Z in learning and using bilingualism (Indonesia-Korea) in their social interactions and what motivation generation Z has in using bilingualism when interacting. Based on this problem, the researcher decided to conduct research in the eastern part of Surabaya. The choice of the area was based on the number of campuses in East Surabaya. This is because students belong to generation Z where they are more open and aware of popular culture such as Korean Wafe. The method used in this research is a qualitative research method with a phenomenological approach. In this research, researchers used Lev Manovich's new media theory and Herbert Blumer's symbolic interactionism theory. This research reveals that the phenomenon of Indonesian-Korean bilingualism is caused by the Hallyu phenomenon, they study Korean culture by taking advantage of the convenience or features available in new media. Apart from that, they use Indonesian-Korean bilingualism based on emotional meaning, identity meaning and self-image meaning.